Bauran Pemasaran Industri Rumah Tangga : sebagai Upaya Transfigurasi di Era Vuca - Eka Rachmawati; Eny Machsusiyah Zin; Muhammad Bima; Peni Nevia Fitri Ami; Fathor AS (Journal of Mandalika Literature, 2024)
The development of the industrial revolution 4.0 era is the cause of progress in various fields, especially the economic sector. The covid-19 pandemic that occurred 4 years ago paralyzed the sector, especially the economic sector, and led to a transformation that can be seen based on VUCA (Volatility, Uncertainty, Complexity, and Ambiguity). This research aims to find out what strategies are carried out by home industri entrepreneurs to increase the number of sales volumes amid the onslaught of VUCA transfomation and provide suggestions or input for what solutions should be done in the home industri company Batang-batang Daya Village, Sumenep Regency. This research uses descriptive qualitative methods with primary data in the form of interviews, documentation, and observation. The technique of taking sample data is done by purposive sampling. The results of the study are the strategies used in the industri can increase business volume in the Household Industri is to use Advertising, sales promotion, personal selling, publicity, and direct marketing. The contribution of this research is that it can help the Household industri in Batang-batang Daya village, Sumenep district in providing solutions to increase sales volume in the midst of the VUCA Era. In addition, this research also contributes to providing information to academics in dealing with problems related to the economy in the VUCA Era.